Dynamic Data Grid Replication Algorithm Based on Weight and Cost of Replica - Zhongping Zhang; Chao Zhang; Mengfei Zuo; Zhiping Wang (Institute of Advanced Engineering and Science, 2014)
Data Grid is composed of a large number of distributed computation and storage resources to facilitate the management of the huge distributed and sharing data resources efficiently. Dynamic replication can reduce the file storage time and use the grid resources effectively in a Data Grid environment. The Data Grid topology is divided into three layers: Regional level, LAN level, the grid site level. We have improved DHRA algorithm in three areas: replica selection, replica placement, replica replacement. Considering the weight and cost of replica, we propose dynamic Data Grid replication algorithm LWLC Based on Weight and Cost of Replica. At last, we use the OptorSim to prove the effectiveness of the LWLC . DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4737